The Role Of Social Protection In Reducing Rural Poverty In Developing Countries (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
This research aims to identify the role that social protection plays in reducing rural poverty in developing countries, by addressing the concept of rural poverty, And identifying social protection mechanisms in Syria and developing countries to reduce rural poverty. This study used a descriptive_ analytical methodology. The study reached many findings, the most important of which are: social protection in many developing countries rely on diverse mechanisms of reducing rural poverty, the most notable of which are food assistance and cash transfers, Public works programs, microfinance, and Food Purchasing Program, and insurance on crops, and agricultural interventions. Syria applied a package of social protection mechanisms in the agricultural sector which aimed to reduce poverty in the Syrian rural. Social protection mechanisms contribute to reducing rural poverty in developing countries. In Liberia, Public works programs managed to reduce the poverty gap by 5 percent. China provided unconditional cash transfers of more than 75 million in rural areas. Before the war, Syria could achieve food security with 100 percent of wheat, grains, vegetables, and fruits. This research recommended benefiting from the Food Purchasing experience in developing countries and trying to apply it locally in the education sector by providing School Meals.